2008
DOI: 10.1158/0008-5472.can-07-5021
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feedback Regulation of IFN-γ Pathway by IFN Regulatory Factor 2 in Esophageal Cancers

Abstract: IFN-; is an antitumor cytokine that inhibits cell proliferation and induces apoptosis after engagement with the IFN-; receptors (IFNGR) expressed on target cells, whereas IFN regulatory factor 2 (IRF-2) is able to block the effects of IFN-; by repressing transcription of IFN-;-induced genes. Thus far, few studies have explored the influences of IFN-; on human esophageal cancer cells. In the present study, therefore, we investigated in detail the functions of IFN-; in esophageal cancer cells. The results in cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…The molecular basis of these effects is the Stat1-dependent activation of gene encoding inhibitors that influence cellular progression (18,19). In contrast, our group found that IFN-Á promotes the proliferation of tumor cells in OSCC.…”
Section: Discussionmentioning
confidence: 94%
“…The molecular basis of these effects is the Stat1-dependent activation of gene encoding inhibitors that influence cellular progression (18,19). In contrast, our group found that IFN-Á promotes the proliferation of tumor cells in OSCC.…”
Section: Discussionmentioning
confidence: 94%
“…However, the regulatory effects of IRF1 and IRF2 on IFN transcription are completely opposite. IRF1 is found to upregulate the expression of IFN-b and IFN-g, whereas IRF2 inhibits this induction, acting as an antagonist for IRF1 (26,28,34). Similarly, IRF4, competing with IRF5 for MyD88 interaction, markedly decreases the induction of proinflammatory cytokines and ISRE-Luc (52).…”
Section: Discussionmentioning
confidence: 99%
“…IRF2 and IRF4 are known negative regulators. IRF2 shares high sequence homology with IRF1 and serves as a transcriptional repressor of expression of IFN and ISGs by competing with IRF1 (26)(27)(28). IRF4 interacts with IRF5 and balances the antiviral responses when host cells were infected by virus (29,30).…”
mentioning
confidence: 99%
“…The inhibitory effect of aGalCer on B16F10 lung metastases, of which IFNg is known to be a critical mediator, is significantly more prominent in mice with mutations in tyrosine-441 of the IFNg receptor subunit 1 (31). The IFNg pathway has been demonstrated to be negatively regulated by IFN regulatory factor 2 in esophageal cancer (32).…”
Section: A Possible Mechanism Underlying the Controversial Effects Ofmentioning
confidence: 99%